Energy conversion through local piezoelectric effect in polymer foams for enhancing sound absorption - Ayman Mahmod Mohamed Khalil Shahin (Nanyang Technological University, 2020)
Airborne sound absorption in porous materials is a complex process that involves multiple working mechanisms of converting mechanical acoustic energy into heat, including thermal effect due to the dynamic heat conduction forced by the rarefaction and the densification of the air, viscous effect caused by the adherence of the fluid at the interface with the solid, and structure’s damping effect with mechanical energy dissipation when the sound wave impacts on the solid. Electromechanically active coupling effect, particularly piezoelectric effect, has so far been studied mainly for structural vibration damping but not for airborne sound absorption. This thesis examines contributions of the electromechanical conversion mechanism to the airborne sound absorption effect, particularly local piezoelectric effect in porous polar materials.